Peningkatan Ketahanan Pakan Ternak Melalui Pembuatan Silase di Desa Pesantren, Kecamatan Blado, Kabupaten Batang - Pudjawati, Nihawa Hajar; Fita Ayu Widyaningtyas; Wisnu Arya Seta; Wafa Mei Diinaa Ibrahim; Ferlisca Sashy Reva; Harwin Fadia Lutfiyatus Sholichah; Dwi Cahyo Sampurno; Hafidz Amiruddin; Retno Cahyakinasih; Komala, Iyep (Jurnal Pusat Inovasi Masyarakat, 2024)
Silage is forage processing done by fermentation using lactic acid under anaerobic conditions. Silage is an alternative animal feed that can fulfil animal feed needs when it is difficult to obtain. The rich nutrient content in silage, such as protein, carbohydrates and minerals can fulfil the nutritional needs of animals and support optimal productivity. This activity aims to provide in-depth knowledge and skills to farmers regarding silage making techniques as quality animal feed. Activities start from information gathering; preparation and making of silage materials, concepts, and samples; preparation and procurement of silage material tools; implementation of socialisation; opening of silage results, and evaluation of activities that have been carried out. This test consists of several variables including; aroma, texture, colour and the presence of fungi. The results of the activity showed an increase in farmers' knowledge about silage making, there were 82% of farmers who understood the material presented and 55% of farmers were very satisfied with the activities that had been carried out. The silage results that have been made show some characteristics that are less in accordance with the category of good quality silage at the top of the silage, but the silage results at the bottom are still in the category that can be accepted by livestock. Good quality silage can be determined through its physical quality, so an organoleptic test is carried out to see the physical quality of silage. The quality of the silage produced based on organoleptic tests has a brownish green colour, a slightly smelly aroma, a slightly watery mushy texture and the presence of fungi in the top layer. Thus, making silage has the potential to be a solution to overcome the problem of feed availability in the dry season and increase the capacity of farmers in managing feed.